Gender differences in education - Tuomas Pekkarinen (Institute for the Study of Labor (IZA), 2012)
This paper surveys the trends in gender gaps in education, their causes and potential policy implications. I show that female educational attainment has surpassed, or is about to surpass, male educational attainment in most industrialized countries. These gaps reflect male overrepresentation among secondary school drop-outs and female overrepresentation among tertiary education students and graduates. Existing evidence suggests that this pattern is a result of a combination of increasing returns to education and lower female effort costs of education. Widening gender gap in education combined with recent wage and employment polarization will likely lead to widening inequalities and is linked to declining male labor force participation. The paper discusses evidence on educational policies that both widen and reduce gender gaps in educational outcomes.
urn:nbn:de:101:1-201206146661
Keywords: I20; J160; J240; 330; education; gender differences; test scores; Bildungsniveau; Bildungsabschluss; Geschlecht; OECD-Staaten